DEVIANCE IN LATGALIAN FOLK-TALES: GENDER ASPECT - Juško-Štekele, Angelika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The aim of the paper is to identify deviant patterns of behavior between wife and husband in Latgalian household folk-tales by rising those characteristic and action strategies, which in accordance with the public assessment are recognized as non-compliant for traditional gender roles. The empirical source of the research is Latgalian household folk-tails, which thematically cover a variety of relationship models peculiar for a family (husband and wife). For the analysis of a deviant feature developed in a story the author applied theory of social action established by the sociologist Talcott Parsons. In the context of a fairy-tale, the actors (a husband and a wife) should not be regarded as individuals in a sense of a separate person, but instead as representatives of the given gender. Therefore, the nature of their actions is not individual as well, but instead more culturally-historically determined, which in accordance with the folk theory proposed by Richard Dorson is “real situation and local environment”. Deviant behavior scenarios in fairy-tales allow to evaluate developmental tendencies of a family as an institute for a period starting with 20th century, when folk-tales chosen for the empirical source were written, up to nowadays, when in the form of strategic documents are raised such problems of family institutes as significant decline in the amount of registered marriages and increase of divorced marriages.